The increasing of enamel calcium level after casein phosphopeptideamorphous calcium phosphate covering - Widyasri Prananingrum; Puguh Bayu Prabowo (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Caries process is characterized by the presence of demineralization. Demineralization is caused by organic acids as a result of carbohydrate substrate fermentation. Remineralization is a natural repair process for non-cavitated lesions. Remineralization occurs if there are Ca2+ and PO43- ions in sufficient quantities. Casein-amorphous calcium phosphate phosphopeptide (CPP-ACP) is a paste material containing milk protein (casein), that actually contains minerals, such as calcium and phosphate. The casein ability to stabilize calcium phosphate and enhance mineral solubility and bioavailability confers upon CPP potential to be biological delivery vehicles for calcium and phosphate. Purpose: The aim of this study was to determine the calcium levels in tooth enamel after being covered with CPP-ACP 2 times a day for 3, 14 and 28 days. Methods: Sample were bovine incisors of 3 year old cows divided into 4 groups, namely group I as control group, group II, III and IV as treatment groups covered with CPP-ACP 2 times a day. All of those teeth were then immersed in artificial saliva. Group II was immersed for 3 days, while group III was immersed for 14 days, and group IV was immersed for 28 days. One drop of CPP-ACP was used to cover the entire labial surface of teeth. The measurement of the calcium levels was then conducted by using titration method. All data were analyzed by One- Way ANOVA test with 5% degree of confidence. Results: The results showed significant difference of the calcium levels in tooth enamel of those groups after covered with CPP-ACP 2 times a day for 3, 14 and 28 days (p = 0.001). There is also significant difference of the calcium levels in tooth enamel of those treatment groups and the control group (p = 0.001). Conclusion: The calcium levels of tooth enamel are increased after covered with CPP-ACP 2 times a day for 3, 14 and 28 days.Latar belakang: Proses terjadinya karies gigi ditandai oleh adanya demineralisasi. Demineralisasi terjadi oleh asam organik sebagai hasil fermentasi substrat karbohidrat oleh bakteri. Remineralisasi adalah proses perbaikan alami untuk lesi non cavitated. Remineralisasi terjadi jika terdapat ion Ca2+ dan PO43- dalam jumlah cukup. Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) adalah bahan berbentuk pasta berisi suatu protein susu (kasein). Pada kasein terkandung mineral kalsium dan fosfat. Kemampuan kasein untuk menstabilkan kalsium fosfat dan meningkatkan kelarutan dan bioavailabilitas sehingga CPP memiliki potensi menghantarkan kalsium dan fosfat. Tujuan: Tujuan penelitian ini untuk mengetahui kadar kalsium enamel setelah pengulasan CPP-ACP pada permukaan enamel 2 kali sehari selama 3,14 dan 28 hari. Metode: Sampel adalah gigi insisif sapi, usia 3 tahun. Pada penelitian ini sampel (n = 24) dibagi menjadi 4 kelompok yaitu kelompok I sebagai kelompok kontrol, dan kelompok II, III, IV sebagai kelompok perlakuan dengan pengulasan CPP-ACP 2 kali sehari. Semua kelompok direndam dalam saliva buatan. Kelompok II direndam 3 hari, kelompok III direndam 14 hari, kelompok IV direndam 28 hari. Pengulasan CPP-ACP sejumlah 1 tetes diratakan pada seluruh permukaan labial gigi. Pengukuran kadar kalsium dilakukan dengan metode titrasi. Semua data dianalisa dengan uji One-Way ANOVA dengan taraf kemaknaan 5%. Hasil: Hasil penelitian menunjukkan perbedaan yang signifikan kadar kalsium enamel gigi di antara kelompok (p = 0,001). Hasil penelitian menunjukkan perbedaan yang signifikan kadar kalsium gigi pada kelompok kontrol dan perlakuan antara lama waktu pengulasan 3, 14, dan 28 hari (p = 0,001). Kesimpulan: Pengulasan CPP-ACP selama 3, 14 dan 28 hari mampu meningkatkan kadar kalsium pada enamel.